2018
DOI: 10.14419/ijet.v7i4.7.20375
|View full text |Cite
|
Sign up to set email alerts
|

Colonization and Investigation of Vibrio Cholera Recombination Protein in E-Coli

Abstract: Background and aim: Vibrio cholerae is a gram-negative bacterial pathogen that causes diarrheal disease. One of the most pathogenic factors of V. cholerae is toxin-coregulated pili. This pilus is required as the first factor in the colonization and bacterial persistence in the small intestine. Materials and Methods: In this study, V. cholerae toxin-coregulated pili A (TCPA) gene was amplified using PCR method. The above genes were purified and then expressed by being cloned into the pGEX4T-1 plasmid. Then the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Environmental changes such as pH or temperature or salt stimulate the onset of gene expression of the bacteria. 92 It has been reported that Vibrio cholera toxin (VCHT) increases the interleukin-6 (IL-6), interleukin-1 (IL-1), and IL-8 secretions. 93,94 This toxin also enhances the release of tumor necrosis factor (TNF-α), 95 extracellular signal-regulated kinases (ERK1/2), and p38 mitogen-activated protein kinases (MAPK).…”
Section: Staphylococcusmentioning
confidence: 99%
“…Environmental changes such as pH or temperature or salt stimulate the onset of gene expression of the bacteria. 92 It has been reported that Vibrio cholera toxin (VCHT) increases the interleukin-6 (IL-6), interleukin-1 (IL-1), and IL-8 secretions. 93,94 This toxin also enhances the release of tumor necrosis factor (TNF-α), 95 extracellular signal-regulated kinases (ERK1/2), and p38 mitogen-activated protein kinases (MAPK).…”
Section: Staphylococcusmentioning
confidence: 99%
“…The use of bagasse ashes in the mixing scheme of concrete increases the water absorption and since bagasse ash from Al2O3 and SiO2 It is rich, the hardening process and clamping of concrete samples are accelerated. Also, the presence of calcium oxide the combination of bagasse ash accelerates the process of hardening and stacking of concrete [43][44][45][46][47][48][49][50]. The influence and displacement of chloride ions depends on the structure and pore of concrete.…”
Section: Figure 2 Chloride Attackmentioning
confidence: 99%
“…The crystal structure of zeolite nanoparticles was confirmed with the powder's X-ray diffraction (XRD) patterns which were recorded on a PAN analytical instrument Empyrean model with a scanning rate of 0.005˚ 2 min -1 in between 6˚ to 45˚ intervals. The morphologies of the zeolite nanoparticles and porous membranes were characterized by scanning electron microscopy (Quanta 250 FEG) (40)(41)(42)(43)(44). To analyze cross section of the membranes, samples were fractured cryogenically in liquid nitrogen and then subsequently coated with gold using a Magnetron Sputter Coating Instrument for 90 s. EDX was used to evaluate the elemental compositions of the nanoparticles and to determine Si/Al ratio.…”
Section: Hybrid Membrane Characterizationmentioning
confidence: 99%